Digital transformation and tax evasion reduction: An empirical study of employee perceptions in the Babil Tax Directorate - Amjed Ismail; Sarah Shakir Ibrahim (Journal of Accounting and Digital Finance, 2026)
This study examines the impact of virtual changes on reducing tax evasion and enhancing tax compliance within Babylon’s tax agencies. Recognizing the conceptual distinction between tax avoidance (criminal planning) and tax evasion (illegal controls), this study focuses specifically on the latter. It takes a descriptive-analytical approach, using a questionnaire to measure attitudes and perceptions among a sample of 172 tax employees, thereby providing validation for the study. The regression analysis revealed a statistically significant impact of digital transformation on the studied variables. Specifically, digitalization explained 54.5% of the variance in perceived reductions in tax evasion and 51.7% of the variance in perceived revenue collection performance. These results indicate that digital transformation can support tax monitoring, improve administrative efficiency, and reduce opportunities for illegal tax practices. The study recommends completing the digital infrastructure and intensifying staff training to optimize the use of this technology.